Involvement of Central Endothelin ETA and Cannabinoid CB1 Receptors and Arginine Vasopressin Release in Sepsis Induced by Cecal Ligation and Puncture in Rats. Issue 3 (September 2016) - Leite-Avalca, Mariane C.G.; Lomba, Luis A.; Bastos-Pereira, Amanda L.; Brito, Haissa O.; Fraga, Daniel; Zampronio, Aleksander R.
Abstract : ABSTRACT: We previously reported that endothelin-1 (ET-1) reduced the frequency of spontaneous excitatory currents in vasopressinergic magnocellular cells through the activation of endothelin ETA receptors in rat brain slices. This effect was abolished by a cannabinoid CB1 receptor antagonist, suggesting the involvement of endocannabinoids. The present study investigated whether the blockade of ETA or CB1 receptors during the phase of increased levels of ET-1 after severe sepsis increases the survival rate of animals concomitantly with an increase in plasma arginine vasopressin (AVP) levels. Sepsis was induced in male Wistar rats by cecal ligation and puncture (CLP). Treatment with the CB1 receptor antagonist rimonabant (Rim; 10 and 20 mg/kg, orally) 4 h after CLP (three punctures) significantly increased the survival rate compared with the CLP per vehicle group. Intracerebroventricular treatment with the ETA receptor antagonist BQ123 (100 pmol) or with Rim (2 μg) 4 and 8 h after CLP but not the ETB receptor antagonist BQ788 (100 pmol), also significantly improved the survival rate. Sham-operated and CLP animals that were treated with Rim had significantly lower core temperature than CLP animals. However, oral treatment with Rim did not change bacterial count in the peritoneal exudate, neutrophil migration to the peritoneal cavity, leucopenia or increased plasma interleukin-6 levels induced by CLP. Both Rim and BQ123 also increased AVP levels 12 h after CLP. The blockade of central CB1 and ETA receptors in the late phase of sepsis increased the survival rate, reduced body temperature and increased the circulating AVP levels.